In vivo XCT bone characterization of lattice structured implants fabricated by additive manufacturing. Issue 8 (August 2017) - Obaton, A-F.; Fain, J.; Djemaï, M.; Meinel, D.; Léonard, F.; Mahé, E.; Lécuelle, B.; Fouchet, J-J.; Bruno, G.
Abstract: Several cylindrical specimens and dental implants, presenting diagonal lattice structures with different cell sizes (600, 900 and 1200 μm) were additively manufactured by selective laser melting process. Then they were implanted for two months in a sheep. After removal, they were studied by Archimedes' method as well as X-ray computed tomography in order to assess the penetration of bone into the lattice. We observed that the additive manufactured parts were geometrically conformed to the theoretical specifications. However, several particles were left adhering to the surface of the lattice, thereby partly or entirely obstructing the cells. Nevertheless, bone penetration was clearly visible. We conclude that the 900 μm lattice cell size is more favourable to bone penetration than the 1200 μm lattice cell size, as the bone penetration is 84% for 900 μm against 54% for 1200 μm cell structures. The lower bone penetration value for the 1200 μm lattice cell could possibly be attributed to the short residence time in the sheep. Our results lead to the conclusion that lattice implants additively manufactured by selective laser melting enable better bone integration.